PENGARUH APLIKASI DOSIS PUPUK HAYATI VP3 DAN LAMA INDUKSI LISTRIK TERHADAP RESPIRASI TANAH DAN HASIL TANAMAN KEDELAI (Glycine max (L) Merr.) - eddrin wahyu febbiliani (AGRONISMA, 2021)
This study aims was to determine the effect of application of VP3 biofertilizer dose and duration of electrical induction on soil respiration on land per soybean plant and soybean yield. The research was conducted in the experimental field of Griya Shanta, Brawijaya University, Malang and Microbiology Laboratory, Islamic University of Malang. The design used was a simple randomized block design (RAK) with 13 treatments which were repeated 3 times. While the observation of soil respiration was carried out using the modified Verstraete method. The results showed that soil respiration tends to be influenced by the application of VP3 biofertilizer. Meanwhile, electric induction did not show a significantly different effect. Biofertilizer VP3 100% gave the highest soil respiration yield (1024.8 mg jm m-1). As for the results of the effect of the best and most efficient treatment, namely V1L2 (VP3 100% + Electric Induction 60 minutes) of 33.32 g of planting.